The effect of commercial banks' internal control weaknesses on loan loss reserves and provisions. Issue 1 (April 2016) - Cho, Myojung; Chung, Kwang-Hyun
Abstract: This study examines whether the material internal control weaknesses (ICW) of commercial banks affect loan loss reserves and provisions. Bank regulators have been keen to improve the internal control procedures of banks in order to obtain accurate estimates of loan loss exposures.GAO (1991, 1994) reports that loan-loss reserves are often determined based on historical loss rates even for large loans, rather than individual loan impairment assessments, and the reported loan loss reserves include substantial amounts of supplemental reserves that are not linked to the loan loss exposure. We expect and find that banks with material ICW have, on average, higher loan loss reserves and provisions in years of ICW than those without ICW. We also find that ICW banks with successful remedial actions no longer have higher levels of loan loss reserves or provisions in the next year, while banks that report material ICW in both the current and following year continue to have significantly higher amounts of loan loss reserves and provisions in the next year.